2010
DOI: 10.1039/c0em00144a
|View full text |Cite
|
Sign up to set email alerts
|

Polycyclic aromatic hydrocarbons in surface sediments from drinking water sources of Taihu Lake, China: sources, partitioning and toxicological risk

Abstract: Sources, partitioning and toxicological risk of 15 priority polycyclic aromatic hydrocarbons (PAHs) in surface sediments from drinking water sources of Taihu Lake, with an area of 2428 km(2) located in the most developed and populated area of China, were studied, and the results were compared with those in other lakes of China and the USA. Concentrations of the 15 PAHs in sediments ranged from 436.6 to 1334.9 ng g(-1) (dw). Gasoline combustion, coal combustion, diesel combustion from shipping and spillage of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(26 citation statements)
references
References 29 publications
1
23
1
Order By: Relevance
“…Chem. 31,2012blooms, and ecosystem degradation [33,34,36]. Most of the water intakes for the surrounding population and the main water source protection zone are located in the northern and eastern parts of the lake, including Meiliang Bay, Gonghu Bay, and Xukou Bay.…”
Section: Sample Collectionmentioning
confidence: 99%
See 2 more Smart Citations
“…Chem. 31,2012blooms, and ecosystem degradation [33,34,36]. Most of the water intakes for the surrounding population and the main water source protection zone are located in the northern and eastern parts of the lake, including Meiliang Bay, Gonghu Bay, and Xukou Bay.…”
Section: Sample Collectionmentioning
confidence: 99%
“…In recent years, Taihu Lake has been subjected to increasing and more serious contamination due to rapid urbanization and industrial and agricultural development. It has been found that Taihu Lake has suffered from accelerated eutrophication resulting from overloading of nitrogen and phosphorus, thereby posing a health risk to the population surrounding the lake [31][32][33][34]. Extensive studies have disclosed a serious deterioration of water quality due to pollutants derived from household, industrial, and agricultural discharge, and several kinds of persistent organic pollutants (POPs) have been detected in air, water, sediment, and even biota in the region.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…17 Then PAHs in the waters should be taken into consideration in order to protect the water resources and human health in this region. A previous study had reported on the spatial distribution of PAHs in waters in the Lake, showing that the total PAHs concentrations in the overlying water and porewater were more than ten thousands ng L À1 and the northern bays were the most polluted areas.…”
mentioning
confidence: 99%
“…However, most of these researches just focused on the spatial characteristics of pollution in surface sediments, and little information about the diffusive flux or toxicological risk of these toxic pollutants in pore water profiles could be acquired. In addition, supplying drinking water for large cities (such as Shanghai City and Wuxi City) is one of the most important functions of Taihu Lake (Tao et al 2010). Therefore, exploring the distribution and risk of toxic pollutants in pore water profiles from the heavily polluted areas of Taihu Lake is necessary to protect these water resources and human health.…”
Section: Responsible Editor: Ester Heathmentioning
confidence: 99%